Investigation of the antimicrobial resistance patterns in Staphylococcus aureus isolated in the milking of cows in the lactation - Zafalon, Luiz Francisco (2008)
The resistance patterns of Staphylococcus aureus isolated from milk of dairy cows with mastitis, teat orifices and mouthpieces of the liners were studied. The samples from the milk and teat orifices were obtained before milking and samples from mouthpieces were obtained before and in the course of milking. The Kirby and Bauer standardized disc diffusion test was performed with previous confirmation of isolates by molecular method. The resistance to penicillin was predominant to the isolates from milk, teat orifices and mouthpieces (48.3%, 36.8% and 25.9%, respectively). The resistance to oxacillin was found in all sources studied, with characteristics of multidrug resistance. The bovine mastitis treatment is recommended after sensitivity tests to the different antimicrobials of microorganisms responsible by aetiology. The identification of strains oxacillin-resistant explains the care with the possibility of transmission of S. aureus by milk.